(untitled) (Global Journal of Science Frontier Research, 2012)
The present discounted value equation in finance has a broad range of uses and may be applied to various areas of finance including corporate finance, banking finance and investment finance etc .The basic premise of present discounted value is the time value money .Not many analytic solutions exist for present discounted value problems but by using Laplace transform we can deduce some of the closed form solutions quite easily. In this note we show how present discounted value in finance related to Laplace transforms. Also we discus on the present value rules for the elementary functions and the general properties of the Laplace transform. And we will focus on the application of time derivative property using Laplace transforms to each present value rule.